Effective Treatment of Veterans With PTSD: Comparison Between Intensive Daily and Weekly EMDR Approaches - Hurley, E. C. (Frontiers in Psychology, 2018)
The effectiveness of EMDR therapy in treating veterans diagnosed with PTSD was evaluated in this study using two treatment formats: intensive daily EMDR treatment provided twice a day during a 10-day period and a second format of one session each week. The study used archived outcome data previously collected and stored at Soldier Center. Both formats provided 18–20 treatment sessions of EMDR therapy to veterans diagnosed with PTSD that included dissociative exhibitions and moral injury issues. Questions addressed included: (1) does EMDR therapy administered twice daily ameliorate veterans’ PTSD symptoms; (2) does EMDR therapy administered twice daily provide equivalent outcome results as EMDR therapy administered weekly for 18–20 sessions; and (3) does the treatment outcome persist. The effectiveness of the weekly treatment group was also evaluated. Both groups’ results were assessed at pre-treatment, post-treatment and 1-year follow-up. The results indicated that both weekly treatment and intensive daily treatment groups produced statistically significant treatment effects (p < 0.001) that were maintained at 1-year follow-up. The10-day EMDR intensive daily treatment (EMDR therapy twice a day for 10 days) produced a similar outcome as to that of the weekly treatment with a 1-year follow-up. Results support the effectiveness of EMDR therapy when offered in both weekly treatment format as well as the intensive 10-day format on an outpatient basis. While recognizing the limitations of this study the results are significant to warrant additional research.